Isaiah 61:1-3(4-9) 10-11 Transferor of privileges, an "identikit" of the servant of the Lord? - Kruger, H. a. J. (HTS teologiese studies, 2002)
On the basis of the demarcation of the book of Isaiah into three distinct literary units, scholarly opinion has ruled out the possibility that Isaiah 61:1-4 (5-9) 10-11 (as part of Trito-Isaiah) might be given the status of a so-called Servant Song along with the other group of “genuine” Servant Songs (Isa 42:1-4; 49:1-6; 50:4-1; 52:13-53:12, as part of Deutero-Isaiah). The paper argues that Isaiah 61 should be integrated with the other four Songs, bringing the number of the Songs of the Servant to five. Arguments to support the case include a profile of the figure in chapter 61 in relation to the one described in the first four Songs; the application of what may be called a “democratization” concept; the mediating function of the figure referred to in Isaiah 61, and the role of the literary structure of the eleven chapters of Isaiah 56-66.